IoT-BASED SYSTEM FOR MONITORING WATER QUALITY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Water-borne infections, such as dengue fever, cholera, and malaria, have emerged as serious healthconcerns in the modern world. Water contamination is responsible for 40% of all deaths worldwide.Drinking water quality must be monitored continuously as it is delivered to customers. This articlepresented a low-cost, real-time water quality measuring system design that leverages the Internet ofThings (IoT). Measurements of the water's temperature, humidity, pH, and turbidity must becalculated. The poisoning of fresh water supplies is probably the green globalization's biggest fear.Constant monitoring of water quality is required to provide a safe supply of potable water. In thispaper, we outline the steps taken and the features added to a framework designed to make it easy tomonitor water quality in real time over the Internet of Things. Multiple sensors, built by a team withexperience in water quality assessment, are integrated into the structure. The variables, such astemperature, pH, turbidity, and humidity. The central controller can configure the sensors'perceptive qualities. The ATMEGA328 can serve as the brains of the operation. In the end, WI-FIarchitecture allows the sensor data to be seen online. A Microcontroller is used as the automationcontroller for this project. When a PC sends data over Wi-Fi, the Wi-Fi module attached to themicrocontroller will pick it up.The Arduino microcontroller links all of the parts together. Allhardware modules receive 5v of DC voltage from a regulated power supply and are controlled by anArduino ATMEGA328 microcontroller programmed in Embedded C using the Arduino IDE